Photo-enhanced field emission studies of tapered CdS nanobelts - Chavan, Padmakar G.; More, Mahendra A.; Joag, Dilip S.; Badadhe, Satish S.; Mulla, Imtiaz S. (2014 27th International Vacuum Nanoelectronics Conference (IVNC), 2014)
Field emission and photo-enhanced field emission characteristics of single crystalline tapered CdS nanobelts have been investigated. The turn-on field for the emission current density of similar to 0.1 mu A/cm(2) is found to be similar to 2.1 V/mu m, which is much lower than reported values for various CdS nanostructures. The photo-enhanced field emission current shows a reproducible photo-switching behavior with rise in current level nearly four times that of its initial preset value (similar to 1 mu A) which is found to be very remarkable. Possible mechanism of photo-enhanced field emission is discussed.
27th International Vacuum Nanoelectronics Conference (IVNC), Engelberg, SWITZERLAND, JUL 06-10, 2014
Keywords: Current stability; field emission; Nanobelts; Photoswitching

Photosensitive field emission study of SnS2 nanosheets (27th International Vacuum Nanoelectronics Conference ) - Joshi, Padmashree D.; Joag, Dilip S.; Rout, Chandra Shekhar; Late, Dattatray J. (2014 27TH International Vacuum Nanoelectronics Conference (IVNC), 2014)
SnS2 nanosheets (SnS(2)NSs), synthesized by one-step hydrothermal reaction, are subjected to Field Emission (FE) studies. For synthesis, specific concentrations of Na2SnO3 and thioamide solution are used. The FE study is carried out in all metal Ultra High Vacuum (UHV) chamber in planar diode configuration at a base pressure of similar to 10(-8) torr. A maximum current density of 110 mu A/cm(2) was attainable. The turn on field required to draw a current density of 1 mu A/cm(2) is found to be 2.6 V/mu m. A separate study was carried out to investigate the photosensitivity of the emitter by illuminating the specimen under visible light. In dark, the FN plot is non-linear, indicative of semiconductor nature of the emitter. However, on illumination, the FN plot is observed to be linear. This remarkable change can be explained by the photoconductivity imparted on illumination. The field at the tip is high in presence of light, than in dark, due to enhanced conductivity. It is also observed that on switching ON the light, the FE current increases almost instantaneously. Repetitive switching is observed at a fixed applied voltage, generating current pulses. The visible light soaking of the sample is carried out by illuminating the lamp for more than 100 minutes, where the current seems to saturate. On switching off the lamp the emission current decayed almost to its initial value exponentially. The photosensitivity has been studied for different wavelengths in the visible spectra. The maximum photosensitive field emission is observed for green filter. With this photoresponse, it is envisaged that SnS2 nanosheets are a potential candidate for optoelectronic applications of field emitters.
Keywords: field emission; photosensitivity; Photoswitching

Photosensitive field emission study of SnS2 nanosheets - Joshi, Padmashree D.; Joag, Dilip S.; Rout, Chandra Shekhar; Late, Dattatray J. (Journal of Vacuum Science & Technology B, 2015)
SnS2 nanosheets (SnS(2)NSs), synthesized by one-step hydrothermal reaction, are subjected to field emission (FE) studies. For synthesis, specific concentrations of Na2SnO3 and thioamide solutions are used. The FE study is carried out in a planar diode configuration at a base pressure of similar to 10(-8) mbar. The emission photosensitivity is also investigated by illuminating the specimen with a visible light source. In dark, the turn on field, the electric field required to obtain a current density of 1 mu A/cm(2), is found to be 5.9 V/mu m. Upon illumination, the emitter with visible light, it is found to reduce to 5.0 V/mu m. A significant change in the nature of the Fowler-Nordheim plot with light illumination is also observed and has been explained on the basis of photoconductivity. Repetitive switching ON and OFF the light source, at a fixed applied voltage, is found to generate current pulses. The photosensitivity is also studied with various color filters. With the photoswitching and the enhanced field emission properties, it is envisaged that SnS(2)NSs possess a potential for optoelectronic applications of field emitters. (C) 2014 American Vacuum Society.